ADHD‐associated PARK2 copy number variants: A pilot study on gene expression and effects of supplementary deprivation in patient‐derived cell lines. Issue 7 (16th August 2022) - Radtke, Franziska; Palladino, Viola Stella; McNeill, Rhiannon V.; Chiocchetti, Andreas G.; Haslinger, Denise; Leyh, Matthias; Gersic, Danijel; Frank, Markus; Grünewald, Lena; Klebe, Stephan; Brüstle, Oliver; Günther, Katharina; et al.
Abstract: Recent studies show an association of Parkin RBR E3 ubiquitin protein ligase ( PARK2 ) copy number variations (CNVs) with attention deficit hyperactivity disorder (ADHD). The aim of our pilot study to investigate gene expression associated with PARK2 CNVs in human‐derived cellular models. We investigated gene expression in fibroblasts, hiPSC and dopaminergic neurons (DNs) of ADHD PARK2 deletion and duplication carriers by qRT PCR compared with healthy and ADHD cell lines without PARK2 CNVs. The selected 10 genes of interest were associated with oxidative stress response ( TP53, NQO1, and NFE2L2 ), ubiquitin pathway ( UBE3A, UBB, UBC, and ATXN3 ) and with a function in mitochondrial quality control ( PINK1, MFN2, and ATG5 ). Additionally, an exploratory RNA bulk sequencing analysis in DNs was conducted. Nutrient deprivation as a supplementary deprivation stress paradigm was used to enhance potential genotype effects. At baseline, in fibroblasts, hiPSC, and DNs, there was no significant difference in gene expression after correction for multiple testing. After nutrient deprivation in fibroblasts NAD(P)H‐quinone‐dehydrogenase 1 ( NQO1 ) expression was significantly increased in PARK2 CNV carriers. In a multivariate analysis, ubiquitin C ( UBC ) was significantly upregulated in fibroblasts of PARK2 CNV carriers. RNA sequencing analysis of DNs showed the strongest significant differential regulation in Neurontin ( NNAT ) at baseline and after nutrient deprivation. Our preliminary results suggest differential gene expression in pathways associated with oxidative stress, ubiquitine‐proteasome, immunity, inflammation, cell growth, and differentiation, excitation/inhibition modulation, and energy metabolism in PARK2 CNV carriers compared to wildtype healthy controls and ADHD patients.